Numerical Simulation of Single-Phase and Two-Phase Flows in Separator Vessels with Inclined Half-Pipe Inlet Device Applied in Reciprocating Compressors - Lucas, F. P.; Huebner, R. (Engineering, Technology & Applied Science Research, 2018)
This paper aims to apply computational fluid dynamics (CFD) to simulate air flow and air flow with water droplets, as a reasonable hypothesis for real flows, in order to evaluate a vertical separator vessel with inclined half-pipe inlet device (slope inlet). Thus, this type was compared to a separator vessel without inlet device (straight inlet). The results demonstrated a different performance for the two types in terms of air distribution and liquid removal efficiency.